“Efecto del control químico sobre phackopsora euvitis y plamopara viticola en vitis labrusca en San Martín- Perú” - Chota Guerra, Gomer Alberto (2014)
The research was conducted in order to evaluate the efficiency of fungicidas in the control of downy mildew (Plasmopara viticola) and Rust (Phakopsora euvitis), the incidence and rate of degree of damage caused by these diseases and offer the grower system chemical, economical, profitable and sustainable control. The experiment was conducted in the Minor Aucaloma populated district of San Roque de Cumbaza province of Lamas, San Martin department Center - Perú.Su Geographic location is between the coordinates of Latitude 06 º South 20'53.5 'West Longitude 76 º 21'21.3 "and Altitude 850 msnmm The implementation period was five months, from February 2014 until June of that year. Designing randomized complete block (RCBD) with 08 treatments and 03 replications was used. The variables were evaluated in the research plan: Total number of branches after pruning, number of flowers per branch, and pathogen performance: lmpact on leaves, severity and intensity of the damage index. Depending on the performance, cost benefit ratio and intensity of damage, fungicidas gave better results are Benalaxyl, Azoxystrobin, Mancozeb + Metalaxyl-M, with application rates of 2g / I, 1 g / I and 3g / I respectively. The most economical treatment for their cost-benefit ratio was the T5 (Benalaxyl), to obtain the lowest cost (47.91%) and return on cost benefit ratio with 2.09 also with the T5 (Benalaxyl). Keywords: vine, rust, mildew, fungicidas, incidence, intensity index damage.